ADAPTASI INOVASI GO-DIGITAL DALAM PELAYANAN PUBLIK PADA MASA PANDEMI COVID-19: (Studi Kasus Dinas Kependudukan dan Pencatatan Sipil Kota Samarinda) - Anita Wahyuni; I Ketut Gunawan; Jauchar Barlian (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2022)
This research focuses on Go-Digital innovation carried out by government institution, by examining forms of innovation, their development, the adaptation of such innovations during the pandemic Covid-19 era, and the results of the innovation adaptation efforts. The object of this research is the Population and Civil Registration Office (Disdukcapil) of Samarinda city, where the data was collected by employing bibliographical research and field work (observation, interviews) and analyzed by using descriptive, qualitative analysis. Research findings show that there are 12 forms of innovation carried out by Disdukcapil where all innovation related to public services. Secondly, Go-Digital innovations 270have been initiated since 2018and continued to be developed until recently for the best results, quantitatively and qualitatively. Thirdly, due to adaptation efforts, the promoted innovation successfully survived during the pandemic era, and even transformed positively in providing public service to the community, indicated by the shorter time needed in delivering public services, service quality can be maintained, and the number of customers do not decrease in general